Mengharmoniskan Hubungan Pelanggan Dengan Karyawan Melalui Kualitas Pelayanan Ditinjau Dari Kinerja PDAM Wilayah Kota Bekasi - Utomo, Kurniawan Prambudi (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2018)
Abstract - This study aims to analyze the influence of the sense of service quality, on the performance of PDAM Bekasi branch. This study aims to determine the effect of reliability, competence, responsive, accesbility and tangible of variables that exist in PDAM Kota Bekasi. The approach used in this research is survey and the type of research is descriptive quantitative. data collection technique by interview, circulate questionnaire to sample used is accident sampling method, sample in this research is 30 respondents and this research conducted during September-November 2017, to test hypothesis used multiple regression by doing assumption test of classical and variable dominant has a significant influence is reliability. Each the influence of variable reliability, competence, responsive, accesbility and tangible to performance is big enough that shows positive and significant value and coefficient value of deterininasi r square) obtained positive and siqnificant, this means that there are the independent variable is able to explain the dependent variable. keywords: reliability, competence, responsiveness, tangible, performance.